Language Anxiety and Achievement among First Year Students of Addis Ababa University, Ethiopia - Bekau Atnafu Taye (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2018)
Abstract The objectives of this study are to measure levels of students' anxiety and to see whether anxiety affects academic their performance. The participants of the study were drawn from the Department of Foreign Languages and Literature at Addis Ababa University (AAU). The study used primary and secondary data and descriptive and inferential statistics. The inferential statistics was made in terms of one-way ANOVA. The results of the study showed that freshman students were anxious, and the level of anxiety affected the performance of the students. It was also found that anxiety and achievement have curvilinear relationships. Ameliorating strategies implied from the findings were also suggested